Online Review And Social Influence: Key Factors In Increasing Impulsive Buying And Self Control As Moderation - Kumala, Masria; Santoso, Adi; Widhianingrum, Wahna (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – Lack of self-control that exists in consumers in making a purchase decision so that impulsive buying often occur which are influenced by external factors. Aim – The purpose of this study is to prove the relationship between online review variables and social influence on impulsive buying and how the role of self-control as a moderation variable on the influence of online reviews and social influence on impulsive buying of Shopee consumers. Design/ methodology/ approach – This research is a quantitative research with a data collection method using a questionnaire distributed via google form to 100 respondents with purposive sampling techniques. Data measurement uses a Likert scale of one to five. The data analysis used in this study is SEM (Structural Equation Modelling) through the SMART PLS 4.0 application with a moderating analysis model. Findings – The results showed that online reviews had a significant effect on impulsive buying of Shopee consumers, social influence not have a significant effect on impulsive buying of Shopee consumers, and self control acted as moderation in the influence of online reviews on impulsive buying, as well as self control doesn’t act as moderation on the influence of social influence on impulsive buying of Shopee consumers. Conclusion - Impulsive buying in e-commerce is solely influenced by online reviews, self-control cannot have an influence on this impulsive buying. So the rhythm of impulsive buying will remain in e-commerce and cannot be stopped. Research implication – This research has important implications for consumers and Shopee companies, it will be useful for consumers when consumers can reduce impulsive habits and strengthen self-control that exists in themselves so that they are able to distinguish buying an item based on needs not wants. Then, it will be useful for the Shopee company, judging from the impulsive habits of Shopee consumers, this can be used as an improved strategy for Shopee to increase sales at the Shopee company. Limitations – This study shows that the results of R-Square are included in the moderate category, so that the influence of the independent variable on the dependent variable is only 29.7%, of which the remaining 70.3% is influenced by other variables